Pelatihan Penanganan Sampah Organik Pasar Induk Kota Meulaboh Menjadi Maggot Sebagai Sumber Pakan Ternak Unggas - Mudastsir; Agam Rizki; Sri Jeksi; Icha Tridayana; Mutawalli; Nailis Salsabila; Nhyra Kamala Putri; Rizki Ambia Rachman; Rizki Erlangga Zanur (CV. Multi Kreasi Media, 2025)
Organic waste is a major component produced at Pasar Induk Kota Meulaboh, which, if not properly managed, can lead to various environmental problems such as soil, water, and air pollution. One innovative solution for managing organic waste is by utilizing Black Soldier Fly (BSF) larvae, also known as maggots. Maggots have great potential in breaking down organic waste into high-value poultry feed. This community service program aims to enhance the understanding and skills of the community, students, and poultry farmers in processing organic waste into maggots through training that covers cultivation techniques, maintenance, and the economic and environmental benefits of maggots. The results of this activity show that utilizing maggots can reduce organic waste volume by up to 60%, while providing a cheaper and more sustainable alternative for poultry feed. Moreover, maggot utilization aligns with the zero waste concept and has the potential to improve local community welfare. However, the adoption of this technology requires continuous support through outreach, facility provision, and collaboration between academics, the government, and the farming community. Organic waste management based on maggots is expected to serve as an effective, environmentally friendly, and sustainable solution for Pasar Induk Kota Meulaboh.